Impact of Talent Management on Employee Performance in Nepalese Commercial Banks - Shrestha, Narendra Kumar (KIC International Journal of Social Science and Management, 2024)
The purpose of this study is to examine the significant insight into the implementation of effective performance methods for organizational success by analyzing the effect of talent management on employee performance in Nepalese private banks. In order to administer the questionnaire and conduct the study, 384 employees of Nepalese private commercial banks in the Kathmandu District were chosen at random using an explanatory research design. To determine the effect of talent management on employee performance, the Statistical Package for the Social Sciences (SPSS) was used to use the statistical regression analytical technique. The resource-based view (RBV) theory is supported by the data’s regression analysis, which demonstrates the significant impact of talent management on employee performance and highlights the necessity of combining performance and effective talent management strategies in order to achieve the goals of successful organizational performance. This study suggests that talent management with comprehensive inclusion strategies must be implemented by practitioners in Nepalese private banks in order to enhance the performance of talented human resources. The study is unique in that it promotes the use of talent management and involvement programs in tandem for successful employee performance tactics.